Multiculturalismo crítico, relações raciais e política curricular: a questão do hibridismo na Escola Sarã - Ozerina Oliveira Victor de; Cláudia Miranda (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2004)
This article takes as its point of departure the complex relations between multiculturalism, affirmative action policies e curricular policies. It recognises that curricular policy takes place in a continuous political circle, and emphasises the political text. It asks if curricular policies are formulated from a multicultural perspective with the objective of understanding the appropriation, which political texts make of multiculturalism and by discussing the visibility, or nonvisibility, of non-whites in such texts. It includes an analysis of the political text of the Sarã School which was the result of a curricular reform carried out in the Municipality of Cuiabá-MT, published in 2000. The analysis considers the verbal text as well as its visual images and recognises that in spite of the presence of multicultural characteristics in its pedagogical presumptions, there are gaps in the verbal text and strong indications of ethnocentrism and racism in the visual part. The presence of racial mixture is also found in the visual images, which, together with the relations of power and the different pedagogical postures present in the text, suggest hybridism as one of the possibilities for a multicultural political text. Key words: critical multiculturalism; race relations; curricular policy Mônica Mota Tassigny Ética e ontologia em Lukács e o complexo social da educação Examina algumas das idéias éticas e ontológicas fundamentais de Georg Lukács como fundamento para a reflexão sobre a educação. Os problemas relacionados ao fenômeno da educação suscitam, no atual momento histórico, um interesse cada vez maior, marcado pela crise estrutural geral da forma de sociabilidade regida pelo capital, da qual resultam crises profundas em variadas instâncias da sociedade. Disso deriva a necessidade de superar, no campo da educação, velhas visões unilaterais dos fenômenos educativos contemporâneos. Independentemente do lugar que se lhe concede a partir de um ponto de vista histórico-social, o complexo social da educação se constitui, a partir de uma perspectiva éticoontológica, como um fato rico, complexo e contraditório, do qual não se pode ter aproximação sem uma sólida base teórica-metodológica.